Racial disparities in in‐hospital outcomes after left ventricular assist device implantation. Issue 10 (15th July 2020) - Ueyama, Hiroki; Malik, Aaqib; Kuno, Toshiki; Yokoyama, Yujiro; Briasouli, Artemis; Shetty, Suchith; Briasoulis, Alexandros
Abstract: Background: Previous studies of patients undergoing various cardiac surgeries demonstrated worse outcomes among African‐American (AA) patients. It remains unclear if the race is a predictor of outcomes among left ventricular assist device (LVAD) recipients. Methods: Patients who underwent LVAD implantation between 2010 and 2017 were identified using the National Inpatient Sample. The race was classified as Caucasians vs AA vs Hispanics, and endpoints were in‐hospital outcomes, length of stay, and cost. Procedure‐related complications were identified via the International Classification of Diseases‐9 (ICD‐9) and ICD‐10 coding and analysis performed via mixed‐effect models. Results: A total of 27 132 adults (5114 unweighted) underwent LVAD implantation in the U.S. between 2010 and 2017, including Caucasians (63.8%), AA (23.8%), and Hispanics (6%). The number of LVAD implantations increased in both Caucasians and AA during the study period. AA LVAD recipients were younger, with higher rates of females and mostly comorbidities, but lower rates of coronary artery disease and bypass grafting compared to Caucasians and Hispanics. Medicaid and median income at the lowest quartile were more frequent among AA LVAD recipients. We did not identify differences in stroke, bleeding complications, tamponade, infectious complications, acute kidney injury requiring hemodialysis, and in‐hospital mortality among racial groups. AA LVAD recipients had lower rates of routine discharge than Caucasians and Hispanics, longer length of stay than Caucasians, but similar cost of hospitalization. After adjustment for clinical comorbidities, race was not a predictor of in‐hospital mortality. Conclusion: We identified differences in clinical characteristics but not in in‐hospital complications among LVAD recipients of a different races.